PERBANDINGAN HASIL ANALISIS CLUSTER K-MEANS DAN K-MEDOIDS UNTUK PEMETAAN MUTU SMK - Intan Juliana Panjaitan; Tiya Wulandari; Budi Susetyo (Jurnal Bayesian : Jurnal Ilmiah Statistika dan Ekonometrika, 2024)
The quality of education in a country is one indicator of the country's progress. Indonesia has formulated an assessment of the quality of education using the National Education Standards (NES). To fulfill the SNP, school accreditation is an obligation that must be fulfilled by all intuitions. The results of the accreditation assessment can be grouped into several groups according to their respective categories. To determine the number of clusters formed, an analysis using the K-Means and K-Medoids methods can be performed with 2 clusters formed. Cluster 1 namely the Provinces of Aceh, Banten, West Kalimantan, Central Kalimantan, North Kalimantan, West Nusa Tenggara, Central Nusa Tenggara, West Sulawesi and Central Sulawesi, and Cluster 2 namely the Provinces of Bali, Bengkulu, DI Yogyakarta, DKI Jakarta, Gorontalo, Jambi, Central Java, East Java, South Kalimantan, East Kalimantan, Bangka Belitung, Riau Archipelago, Lampung, Maluku, North Maluku, Papua, West Papua, Riau, South Sulawesi, Central Sulawesi, North Sulawesi, West Sumatra, South Sumatra, North Sumatra